Penggunaan Bahasa Gaul pada Komentar Media Sosial Instagram: Sebuah Kajian Sosiolinguistik: The Use of Slang in Instagram Social Media Comments: A Sociolinguistic Study - Devit Ita Kurniawati; Atiqa Sabardila (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The development of self-existence and the strengthening of communal relations in cyberspace are now widely facilitated by slang, particularly on Instagram. The high adoption of this language variation is directly proportional to the younger generation's massive digital activity, making it more than just a regular communication tool. Based on this phenomenon, this research analyzes the sociological function of this non-standard vocabulary. Evaluations were conducted to examine the factors that trigger its use, how users project their identities, and its implications for the Indonesian language's existence. Content analysis procedures were applied to analyze qualitative data collected through observation and documentation. Within a descriptive sociolinguistic framework, the object of observation focused on the practice of using slang vocabulary within the Instagram ecosystem. Text samples, both user comments and main posts, were collected from digital activity history over six years (2020–2026). The research findings indicate that non-formal varieties play a dual role in the cyber ecosystem. They not only serve as channels for creative expression but also function as markers of community solidarity and as instruments for strengthening social distance between individuals. The use of slang also impacts the development of Indonesian vocabulary, both through the addition of new terms and shifts in meaning. The strong dominance of public figures (influencers) and online communities has been shown to play a significant role in normalizing slang on the internet. Of course, this escalation also aligns with the movement of pop culture and the ongoing trends on social media. Thus, slang on Instagram is a linguistic phenomenon that reflects the social dynamics of society in the digital age.